Rhetoric Means of a Didactic Amharic Poem from Wärrä Babbo - Wetter, Andreas (Aethiopica, 2012)
This article describes aspects of an Amharic manuscript from Wärrä Babbo written in aǧäm, i.e. in the Arabic script. Since this kind of literature is quite widespread in the eastern parts of Wällo and in Yifat, the article begins with an introductive overview of aǧäm literature in Ethiopia and the special position of eastern Wällo as centre of Islamic scholarship and its role for the development of religiously inspired literacy. The philological and linguistic aspects of this type of Amharic literature are exemplified with a tawḥīd poem from eastern Wällo. Besides a detailled treatment of peculiar linguistic feature of the language used in the poem the analysis of the linguistics means that are used by the author to convey his intentions, i.e. the teaching of the basic Islamic tenets to his illiterate co-religionists, form the central content of the article.